Analisis Konten Edukasi Kesehatan Ibu Hamil pada Akun Instagram @theasianparent_id dalam Perspektif Digital Health Communication - Tia Ayulia; Devy Putri Kussanti; Keriyono . (Journal of Media and Communication | E-ISSN : 3063-9581, 2026)
This study examines maternal health education content on the Instagram account @theasianparent_id, one of the largest parenting platforms in Indonesia with nearly one million followers. The high reliance of pregnant women on Instagram as a source of prenatal information raises serious concerns about content quality, given that not all posts can be guaranteed to be accurate or appropriate for the target audience. This study aims to analyze maternal health education content on the @theasianparent_id account based on four principles of Digital Health Communication (DHC): accessibility, accuracy, relevance, and comprehensibility, as well as to identify how maternal health messages are conveyed within such content. A qualitative approach with a descriptive-interpretive content analysis method was employed, supported by in-depth interviews with three informants consisting of one active midwife as the key informant and two pregnant women or newly postpartum mothers as additional informants. The unit of analysis comprised seven content pieces published from January to March 2026. Findings indicate that relevance was fulfilled most consistently across all content, while accuracy emerged as the weakest dimension since the majority of content did not include verified medical sources. Accessibility was generally well fulfilled, except in content that used technical medical terminology without prior explanation. Message comprehensibility varied by content format, with collaboration reels featuring professional medical personnel demonstrating the highest comprehensibility. This study concludes that @theasianparent_id has not implemented its capacity as a digital health communication medium uniformly and consistently.